Cement Casting to Optimize Reconstruction of Chronic Osteochondral Lesions of the Talus. Issue 4 (August 2017) - Pulgar, Jorge; Escudero, Mario; Carcuro, Giovanni; Schiff, Adam; Pellegrini, Manuel
Few surgical techniques have been described for reconstruction in massive osteochondral lesions of the talus, and there is limited evidence of techniques for accurately reproducing native talar anatomy with bone auto/allograft techniques. In this article, we present a novel technique, which is highly reproducible, using bone cement to restore the congruence and anatomy of the ankle joint. Levels of Evidence : Level V: Technical tip